ANALISIS RASIO RENTABILITAS DAN RASIO LIKUIDITAS PADA BANK BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2008-2014 - Muhammad Ari Sumitra; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
In assessing the financial health of banks and achievement, financial analysis requires several benchmarks. Benchmark that is often used is the ratio or index. Financial ratio analysis conducted to obtain financial information that has achieved a firm.Analysis of financial performance contained in Bank Indonesia Circular Letter No. 6/23 / DPNP is a calculation using the ratio of profitability and liquidity. The profitability ratio is the ratio used to look at the bank's ability to generate profits with the bank’s assets. While the liquidity ratio is the ratio used to look at the bank's ability to pay short-term obligations.The location of research in this study is IDX branch offices Pekanbaru located in Jalan Sudirman No. 73. The purpose of this study was conducted to determine the profitability and liquidity determine the performance of the state-owned bank listed on the Indonesia Stock Exchange 2008-2014.In this study, the methodology used is descriptive method, by describing the conditions of using the company's working capital ratio of profitability and liquidity. The sampling technique used in this study is nonprobability sampling, the purposive sampling technique collecting data through documentation that is done by examining and studying the documents that are relevant to the interests of research. Reference documents are the company's financial statements 2008 to 2014.From the results of data analysis using financial ratio analysis that include liquidity ratios, profitability ratios, the ratio of bank business risks, capital adequacy ratio, and the ratio of business efficiency. It can be concluded that the profitability ratio in state banks and the overall experience fluctuations can be quite good.Keywords: Profitability Ratio, Liquidity Ratio